Pengembangan Media Pembelajaran Berbasis Android Game Education dalam Meningkatkan Motivasi Belajar Peserta Didik SMAN 1 Kedondong Lampung - Aryani Dwi Kesumawardani; Agung Nurhidayat Denhi; Raicha Oktafiani (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: Android-based learning media game education has not been implemented at SMAN 1 Kedondong Lampung, and the learning process has not developed, so students lack motivation in learning. The purpose of this research is to determine the feasibility of android game education-based learning media and to find out the development of game applications on android devices as a learning medium. Using the Research and Development (R&D) method with the simple software MIAT APP INVENTOR. The results of the study indicate that android-based learning game education in increasing students' learning motivation is very feasible and students are very fond of this android-based learning model which is a new learning model for the students themselves and of course for the school as well with a result of 80.2% of the category is very feasible. Thus, it can be concluded that android game education-based learning media can increase students' learning motivation. So it can be suggested that to increase students' motivation to learn, develop learning media based on android game education in schools. Keywords: Development of Android-Based Learning Media, Game Education, Student Learning Motivation Abstrak: Media pembelajaran berbasis android game education belum diterapkan di SMAN 1 Kedondong Lampung, dan proses pembelajaran belum berkembang, sehingga peserta didik kurang motivasi dalam belajar. Tujuan penelitian ini untuk mengetahui kelayakan media pembelajaran berbasis android game education dan ingin mengetahui pengembangan aplikasi game pada perangkat android sebagai media pembelajaran. Menggunakan metode Research and Development (R&D) dengan software sederhana MIAT APP INVENTOR. Hasil penelitian mengindikasi bahwa pembelajaran berbasis android game education dalam meningkatkan motivasi belajar peserta didik sangat layak dan peserta didik sangat menggemari model pembelajaran berbasis android ini yang merupakan merupakan model pembelajaran baru bagi peserta didik itu sendiri dan tentu terhadap sekolahannya juga dengan hasil 80,2 % kategori sangat layak. Dengan demikian dapat disimpulkan bahwa media pembelajaran berbasis android game education dapat meningkatkan motivasi belajar peserta didik. Sehingga dapat disarankan bahwa untuk meningkatkan motivasi belajar peserta didik maka kembangkanlah media pembelajaran berbasis android game education di sekolah. Kata kunci: Pengembangan Media Pembelajaran Berbasis Android, Game Education, Motivasi Belajar Peserta Didik